Penyuluhan Pemberdayaan Ibu Hamil dalam Pencegahan Anemia melalui Edukasi dan Konsumsi Tablet Tambah Darah di Puskesmas Ponrang Kabupaten Luwu: Darniati, Zamli - Haddade, Darniati; zamli, zamli (PABBURA : Health Service Journal, 2025)
Anemia in pregnant women remains a serious health problem in Indonesia, with a prevalence reaching 48.9% (Riskesdas, 2021). Anemia poses risks of pregnancy complications such as premature delivery, low birth weight babies, and maternal mortality. This community service activity aims to increase knowledge and compliance of pregnant women in anemia prevention through education and consumption of iron supplementation tablets (TTD). The implementation method was conducted through interactive lectures, discussions, and distribution of leaflets to 50 pregnant women at Ponrang Health Center, Luwu Regency. Evaluation was conducted through pre-test and post-test. Results showed a 90% increase in knowledge and active participation of participants in discussions reached 85%. This activity was effective in increasing awareness and compliance with TTD consumption. It is recommended that this educational activity be conducted continuously. Keywords: anemia, pregnant women, education, iron supplementation tablets.